Biology of IL-36 Signaling and Its Role in Systemic Inflammatory Diseases - Yuan, Zhi-Chao; Xu, Wang-Dong; Liu, Xiao-Yan; Liu, Xing-You; Huang, An-Fang; Su, Lin-Chong (Frontiers in Immunology, 2019)
Interleukin-36 (IL-36) is a member of the IL-1 superfamily and includes 3 agonists (IL-36α, IL-36β, and IL-36γ) and an antagonist (IL-36Ra). IL-36 agonists bind to heterodimeric receptor complexes. Then, the heterotrimer complexes signal via intracellular functional domains, binding to downstream signalling proteins and inducing inflammatory responses. In this review, we summerized the current knowledge about the biologic role of IL-36 and its correlation with systemic inflammatory diseases. The information collected will help to increase the understanding the potential of IL-36 and may give clues for developing novel therapeutic strategies.